Electronic mail forensics - Markagić, Milorad S. (Vojnotehnički glasnik / Military Technical Courier, 2013)
In a general sense, digital forensics could be defined as a compilation of methods of collecting, analysis and presentation of digital evidence that could be found on computers, servers, in networks, databases, mobile devices and all other electronic devices where data is stored. This paper explains methods of collection of digital evidence in electronic mail, their analysis, as well as taxonomy (classification) of digital forensics.